Proceedings of the International Conference on Underwater Networks &Amp; Systems 2019
DOI: 10.1145/3366486.3366523
|View full text |Cite
|
Sign up to set email alerts
|

Real-time Image Enhancement for Vision-based Autonomous Underwater Vehicle Navigation in Murky Waters

Abstract: Classic vision-based navigation solutions, which are utilized in algorithms such as Simultaneous Localization and Mapping (SLAM), usually fail to work underwater when the water is murky and the quality of the recorded images is low. That is because most SLAM algorithms are feature-based techniques and often it is impossible to extract the matched features from blurry underwater images. To get more useful features, image processing techniques can be used to dehaze the images before they are used in a navigation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Wenjie Chen et al [152] offered a technique to obtain quality photos of underwater localization since previously-reported algorithms, such as simultaneous localization and mapping (SLAM), lacked feature-based extraction qualities, resulting in fuzzy images. To address this issue, a novel technology called visual SLAM employs generative adversarial networks to improve picture quality using assessment criteria.…”
Section: Underwater Vehiclesmentioning
confidence: 99%
“…Wenjie Chen et al [152] offered a technique to obtain quality photos of underwater localization since previously-reported algorithms, such as simultaneous localization and mapping (SLAM), lacked feature-based extraction qualities, resulting in fuzzy images. To address this issue, a novel technology called visual SLAM employs generative adversarial networks to improve picture quality using assessment criteria.…”
Section: Underwater Vehiclesmentioning
confidence: 99%
“…Performance evaluation shows the effectiveness of the proposed algorithm for AUVs. Wenjie Chen et al [221] presented the solution to acquire quality images for localization underwater, as already presented algorithms such as SLAM (Simultaneous Localization and Mapping) do not have feature-based extraction quality, which often leads to blurry images. To cater to this issue, a new technique, visual SLAM using Generative Adversarial Networks (GANs), to improve the quality of images by evaluation metrics was introduced.…”
Section: Application To Underwater Vehiclesmentioning
confidence: 99%
“…This line of research has mostly taken place in the computer vision fields, with the main focus on underwater single image restoration Akkaynak and Treibitz (2019); Islam et al (2020b). Benefiting from the superior performance of GAN-based approaches, some researchers attempted to use CycleGAN to boost the performance of ORB-SLAM in an underwater environment Chen et al (2019). The experimental results have shown that CycleGAN-based underwater image enhancement can lead to more matching points in a turbid environment.…”
Section: Introductionmentioning
confidence: 99%